The story of greenburgh school district no. 8 - Fitch, George F.; Haskins, K.; Greenburgh School District, Hartsdale, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1962)
In an attempt to provide actual integration in every school, the Greenburgh School District in New York abolished neighborhood schools and for the past 12 years all children of a given grade have attended the same school. A project for culturally deprived students has recently been instituted to provide a better understanding of an education for an estimated 300-350 children. The efforts to provide actual integration within the school system is based on a desire to meet the needs and interests, and abilities of each individual child within an integrated school. All qualities and kinds of abilities are to be determined, developed and challenged by the school. The design of curriculum organization, activities and program must be geared in this direction. Brief reports are made as to the progress of the project to provide better education for the culturally deprived. Studies are not in progress for evaluation of the program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Desegregation Effects; Disadvantaged Youth; School Desegregation; Student Improvement; Teacher Workshops; New York -- New York (Hartsdale) -- New York (New York)